2018
DOI: 10.21037/jgo.2018.08.12
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with omega fatty acids increases the mRNA expression level of PLA2G4A in patients with gastric cancer

Abstract: Background: Many lines of evidence suggest that arachidonic acid (AA)-based eicosanoid signaling pathway involved in development and progression of human cancers. Cytosolic phospholipase A2-α (cPLA2α) encoded by the PLA2G4A gene acts as an upstream regulator of eicosanoid signaling pathway through providing intracellular AA. The current study aimed to evaluate the effect of omega fatty acids on mRNA expression level of PLA2G4A in patients with gastric cancer (GC) and to assess the possible relation between its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…FGB 85 has been known to be involved in gastric carcinoma. Phospholipase A2 group IVA ( PLA2G4A ), 86 FGG , 87 thymidylatesynthetase ( TYMS ), 88 RAB32 , 89 SEPTIN4 , 90 TPM2 , 91 acyl-CoA thioesterase 7 ACOT7 , 92 phosphoribosyl transferase domain containing 1 ( PRTFDC1 ), 93 Cdk5 and Abl enzyme substrate 1 ( CABLES1 ), 94 major histocompatibility complex, class II, DM beta ( HLA-DMB ), 95 protein tyrosine phosphatase receptor type C ( PTPRC ), 96 CD5 molecule ( CD5 ), 97 CD6 molecule ( CD6 ), 97 membrane spanning 4-domains A1 ( MS4A1 ), 98 CD22 molecule ( CD22 ), 99 CD27 molecule ( CD27 ), 100 mannose receptor C type 2 ( MRC2 ), 101 C-type lectin domain family 2 member D ( CLEC2D ), 102 EEF1A1, 103 and apolipoprotein B ( APOB ) 104 have a significant prognostic potential in various types of cancer. Sphingomyelin phosphodiesterase 1 ( SMPD1 ) 105 expression in colorectal cancer results in drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…FGB 85 has been known to be involved in gastric carcinoma. Phospholipase A2 group IVA ( PLA2G4A ), 86 FGG , 87 thymidylatesynthetase ( TYMS ), 88 RAB32 , 89 SEPTIN4 , 90 TPM2 , 91 acyl-CoA thioesterase 7 ACOT7 , 92 phosphoribosyl transferase domain containing 1 ( PRTFDC1 ), 93 Cdk5 and Abl enzyme substrate 1 ( CABLES1 ), 94 major histocompatibility complex, class II, DM beta ( HLA-DMB ), 95 protein tyrosine phosphatase receptor type C ( PTPRC ), 96 CD5 molecule ( CD5 ), 97 CD6 molecule ( CD6 ), 97 membrane spanning 4-domains A1 ( MS4A1 ), 98 CD22 molecule ( CD22 ), 99 CD27 molecule ( CD27 ), 100 mannose receptor C type 2 ( MRC2 ), 101 C-type lectin domain family 2 member D ( CLEC2D ), 102 EEF1A1, 103 and apolipoprotein B ( APOB ) 104 have a significant prognostic potential in various types of cancer. Sphingomyelin phosphodiesterase 1 ( SMPD1 ) 105 expression in colorectal cancer results in drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hudson et al [ 36 ] found that the impact of PLA2G4A on brain phospholipid metabolism is closely related to the occurrence of schizophrenia. PLA2G4A has also been shown to have a clear preference for membrane phospholipids to catalyze AA, thus playing an important role in the occurrence and progression of various types of cancer[ 7 , 29 , 31 , 37 ]. PLA2G4A is increasingly being implicated in the onset and progression of diabetes, blood disorders, and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The eicosanoid signaling pathway based on arachidonic acid (AA) is involved in the development of human cancer. The cytoplasmic phospholipase A2-α (cPLA2α) encoded by the PLA2G4A gene acts as an upstream regulator of the eicosanoid signaling pathway by providing intracellular AA ( Bazhan and Khaniani, 2018 ). Studies have shown that the PLA2G4A gene can be used as a biomarker in various diseases such as gastric cancer ( Bazhan and Khaniani, 2018 ), acute myeloid leukemia ( Hassan et al, 2021 ; Lai et al, 2021 ), cholangiocarcinoma ( Sun et al, 2019 ), and colorectal cancer ( Zhan et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasmic phospholipase A2-α (cPLA2α) encoded by the PLA2G4A gene acts as an upstream regulator of the eicosanoid signaling pathway by providing intracellular AA ( Bazhan and Khaniani, 2018 ). Studies have shown that the PLA2G4A gene can be used as a biomarker in various diseases such as gastric cancer ( Bazhan and Khaniani, 2018 ), acute myeloid leukemia ( Hassan et al, 2021 ; Lai et al, 2021 ), cholangiocarcinoma ( Sun et al, 2019 ), and colorectal cancer ( Zhan et al, 2021a ). PLA2G4A activates the colorectal cancer microenvironment to produce pro-cytokines IL-17A and adenosine, thereby establishing an effective immunosuppressive microenvironment and promoting immune evasion and tumor metastasis ( Zhan et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%